Strengthening Citizenship Skills in the Context of Digital Citizenship (A Descriptive Study of TikTok Social Media User Students at FKIP Untirta) - Ibtisam, Muhammad Gilang Bayana; Bahrudin, Febrian Alwan; Untari, Aryanti Dwi (Lembaga Riset Mutiara Akbar, 2025)
In the digital era, citizens have the responsibility to actively participate in their communities and contribute to sustainable development. Digital technology has had a significant impact on various aspects of life, including citizenship. Digital citizenship refers to a person's ability to participate ethically and responsibly in the digital environment. Citizen skills in the context of digital citizenship include digital literacy, critical thinking, ethical online interactions, and understanding digital policies. A research study focused on strengthening citizen skills in the context of digital citizenship, using quantitative methods with a descriptive approach. The study surveyed 100 active students at Faculty of Teacher and Education Sultan Ageng Tirtayasa University and found that over 60% of respondents demonstrated proficiency in the five indicators of digital citizenship. Citizenship skills enable citizens to adapt to the digital era, fostering active participation in public decision-making and constructive public interaction. This research emphasizes the importance of developing these skills to become good digital citizens.